Food Safety, Consumer Behaviour, and Government Policy after the COVID-19 Pandemic in Thailand: A Review - Pimoljinda, Thanawat; Hongwiset, Sunee (KnE Social Sciences, 2023)
This paper focuses on the state of food safety and economic recovery in Thailand following the COVID-19 pandemic. Content analysis on the news, research studies, organizations’ reports, and statistical data regarding food safety and relevant government policies during 2020–2022 was employed in order to analyse the impact upon and the adaptation of farmers and consumers, as well as the actions of the Thai government. COVID-19 resulted in various public health measures that placed restrictions on transportation, directly and indirectly affecting the supply chain system, food production, and employment. The Thai government has launched strategic policies based on the Bio-Circular-Green (BCG) economic model in order to recover the overall economic situation. It has supported the University to Tambon’s (U2T) projects with the aim of strengthening the local communities across Thailand. Technological and innovative techniques and equipment have been adopted to create safe food production, especially agricultural products. The project’s development is still underway and needs long-term evaluation and improvement. Keywords: food safety, post COVID-19, economic recovery, U2T campaign